ADAPTIVE PHYSICAL CULTURE IN THE SVERDLOVSK REGION: PROBLEMS OF SUPPORT AND PROSPECTS FOR FINANCING - Polyakova E.Yu.; Knyazeva E.G.; Yuzvovich L.I.; Naboychenko E.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the dynamics and structure of financing the sphere of adaptive physical culture at the regional level. Methods and structure of the study. Reports on the implementation of the state program "Development of physical culture and sports in the Sverdlovsk region until 2024" were taken as material for studying the financing mechanism of physical culture and adaptive physical culture for 2017-2021. Results and conclusions. On the basis of statistical information, it has been established that the share of financing of adaptive physical culture from all expenses of the state program roughly correlates with the share of people with disabilities in the region, but it must be taken into account that not all people with disabilities are registered people with disabilities. Therefore, the allocated funding is not enough to support this category of the population. The current sources of financing for adaptive physical culture are the federal, regional and local budgets, with a predominance of regional budget expenditures. Extra-budgetary sources are indicated as one of the sources of funding for other activities of the state program, which are not attracted to support adaptive physical culture. In the course of the study, the authors consider ways to attract extrabudgetary sources to improve the financing mechanism for adaptive physical culture. One of these methods is public-private partnership, which contributes to the creation of high-quality public infrastructure and the provision of various services based on the property being created.